Potential health risk of areca nut consumption: Hazardous effect of toxic alkaloids and aflatoxins on human digestive system. (December 2022) - Kong, Dandan; Wang, Gaofeng; Tang, Yang; Guo, Mengyue; Ul Haq Khan, Zia; Guo, Yifei; Gu, Wei; Ma, Yonggui; Sui, Ming; Li, Jinping; Yang, Meihua
Graphical abstract: Highlights: Aflatoxins and toxic alkaloids were respectively detected in areca nut products. A high estimated bioaccessibility increased cancer risk in gastric and oral phase. 25.93 % of areca nut was contaminated with aflatoxins that could triple the MRLs. No clear interactive effect existed between alkaloids and aflatoxin in areca nut. Cytotoxicity and MOE risk posed threat for children consuming processed areca nut. Abstract: Contemporarily, there has been a growing consumption rate of areca nut (AN) products worldwide, despite the fact that both fresh and processed AN contain various hazardous ingredients, including toxic alkaloids and carcinogenetic aflatoxins. However, there is a dearth of toxicity and potential cancer risk information regarding toxic alkaloids and aflatoxins via consuming AN products. The present study conducted a comprehensive assessment of the combined hazardous effects of AN alkaloids and aflatoxins towards human digestive system, by methods of HPLC analysis, cell study and in vitro digestive system study. The results revealed a synergetic effect of arecoline and aflatoxins was on human gingival normal fibroblast cell of HGF-1 and a proliferation effect on human tongue squamous carcinoma cell of CAL-27. Specifically, the residual arecoline was as high as 91.08 μg·ml −1 in oral phase and 72.41 μg·ml −1 in gastric phase, which could be an evidence of oral cancer. More importantly, 25.93 % of AN products were contaminated with aflatoxins and the maximum value was three times the MRLs. Under these circumstances, the cytotoxic and MOE values raised a considerable health concern in terms of malignancy risk for children that consume processed AN product, especially compared to scenarios that involve adults and/or fresh AN samples. This study would give rise to a better understanding of the hazards associated with AN alkaloids and aflatoxins towards digestive system, and thus to predict the potential carcinogenic risk of AN products.